Khaki Shadows : Pakistan 1947-1997 - Arif, K. M. (Khalid Mahmud) General, 1930- (Karachi, Pakistan Oxford University Press, 2004)
This title portrays the role of the army in the politics of Pakistan from its earliest years, and how the intermix of political amd military forces created difficulties for both and damaged national prestige.
Include Illustration, Map, Epilogue and Index
Keywords: Pakistan -- Politics and government -- Arif, K. M. (Khalid Mahmud), 1930- -- Armed Forces--Political activity -- Generals--Political activity